Torn between Two Lovers: German Policy on Economic and Monetary Union, the New Hanseatic League and Franco-German Bilateralism. Issue 2 (3rd April 2022) - Howarth, David; Schild, Joachim
Abstract : German governments and European Union (EU) member states forming the New Hanseatic League (HL) have had very similar preferences on EU / Eurozone financial support mechanisms. We would expect German and HL governments to be close allies on these matters. However, empirically, we detect differences. German governments have repeatedly resisted participating in HL joint positions on EU financial support mechanisms and accepted compromises with France. In order to explain this divergence we consider the relative explanatory merit of economic preferences, based on both material interests and economic ideas—here ordoliberalism—on the one hand, and norms of cooperation—here Franco-German 'embedded bilateralism'—and geo-strategic interests on the other hand. We disentangle economic preference formation and the choice in favour of a political strategy to pursue these preferences. Economic preferences are one factor explaining the extent of concessions made by Germany to the HL countries and France. However, norms of cooperation and geostrategic interests explain the choice of German governments on how and with whom best to pursue their preferences. German governments have performed a balancing act between the HL and France, skewed towards the latter. The presence of economic crises increases the degree to which this balancing act is skewed towards France.